The Baltic Finnish peoples divided by state and administrative borders: territorial development of the Karelians, Vepsians, and Setos - Manakov, Andrei G.; Terenina, Natalia (Baltic Region, 2017)
Ethnocultural diversity of the Russian Federation is not only an important component of its historical heritage but also a significant resource for development. However, a number of ethnic groups are on the brink of extinction. The aim of this study is to investigate the impact of changes in state and administrative borders on the territorial and demographic development of small ethnic groups. The article analyses the case of three Baltic Finnish peoples living in the Russian North-West and divided by borders of different levels: Karelians (Finland, the Republic of Karelia, and the Leningrad and Tver regions), Vepsians (the Republic of Karelia and the Leningrad and Vologda regions), and Setos (Estonia and the Pskov region). The analysis is based on the cartographic and statistical demographic data, as well as the results of a complex expedition made in summer 2014 in the Pechory district of the Pskov region. The results of the study show that the assimilation of peoples divided as a result of migration and di vision of their ethnic territory by political borders takes place at an accelerated rate. The study makes it possible to formulate certain recommendations and improve the measures to maintain the language and culture of ethnic minorities of the Russian North-West.